Dietary intake in track and field athletes during a competitive training period - Sillero Quintana, M.; Garcia-Aparicio, A.; Torres-Garcia, A.; Garrido Pastor, G. (Archivos de medicina del deporte, 2008)
Optimal nutrition contributes to achieve maximum sport performance. In competitive period, athletes have to get the right amount of energy and ensuring an adequate intake of micronutrients. Purposes of this study were to analyse dietary habits in female (F) and male (M) elite athletes during a competitive period. We hypothesize that Spanish athletes do not intake a healthy and adequate diet. Subject and methods: Sample included twenty Spanish elite athletes (Table 1). Diet composition was estimated by food weighing (Mettler-Toledo, 0.5g accuracy) for a 5 day period. During the same days, athletes completed a 24h activity questionnaire in order to estimate physical activity level and provide energy expenditure requeriments (EER) (Food and Nutrition Board, 2006). Results: Energy intake and EER were higher in male than female athletes (Table 2). Absolute intake (g/day) for carbohydrates and lipids were also higher in the male group. Cholesterol intakes were higher than maximal suggested in both groups. Micronutrient intakes were suboptimal (Food and Nutrition Board, 2006) for vitamin-E (57% & 65%), vitamin-D (53% & 51%), vitamin-K (87% & 79%), potassium (69% & 90%) (p<0.05) and magnesium (88% & 93%) in F & M respectively. Moreover, female diet`s content for folate (89%) and calcium (88%) did not reach recommendations, and the later was lower than male intake (p<0.01). Conclusions: Considering the last recommendations for competitive period (Burke, Maughan, & Shirreffs, 2007) marginal carbohydrates and elevated lipids intakes were found in both groups. Although female athletes intaked less energy and higher levels of marginal micronutrients, however, their nutrient density values were similar than in males. Female athletes have to increase calcium intakes, this aim coul be got throught an increase in fortifi ed calcium food items consumption. We think that nutritional counselling, intervention and education would be required in order to generate effective changes in the diet quality of these athletes.